Social VR as a Communication Medium: A Systematic Review of Two Decades of Virtual Adaptation in Social Interaction - Sandi, Renda; Kalfin (International Journal of Linguistics, Communication, and Broadcasting, 2025)
Social Virtual Reality (Social VR) has evolved from a theoretical concept to a sophisticated communication medium over the past two decades. This systematic literature review synthesizes 78 peer-reviewed studies published between 2004-2024 to examine the development of Social VR as an interpersonal communication platform. The research employs a PRISMA-guided methodology to investigate five key research questions covering avatar-mediated communication, non-verbal cues, collaborative applications, ethical challenges, and inclusivity aspects. The findings reveal that Social VR has transcended its initial perception as an isolating technology to become a rich, multimodal communication medium that supports embodied presence and immersive interactions. Avatar-mediated communication demonstrates the Proteus Effect, where digital representation influences user behavior and self-perception. Non-verbal cues including gestures, spatial proximity, and gaze direction significantly enhance co-presence and emotional expression beyond traditional video conferencing. Collaborative applications in scientific research, education, and professional settings show improved engagement and knowledge retention through 3D immersive environments. However, significant challenges persist including limited facial expression tracking, inadequate real-time moderation systems, and ethical concerns regarding virtual harassment and privacy. The review identifies accessibility barriers related to device costs, digital literacy, and geographic disparities in research representation. Despite these challenges, Social VR demonstrates remarkable inclusive potential, particularly benefiting elderly users, neurodiverse individuals, and non-verbal communicators who adapt gesture-based and emoji-mediated interactions. The thematic synthesis reveals five primary domains shaping Social VR development: avatar communication, non-verbal interaction, virtual collaboration, ethical considerations, and inclusivity. Future research directions emphasize the need for longitudinal studies on team trust, cross-cultural trials in diverse contexts, AI-enhanced moderation systems, and standardization of expressive avatar technologies. The study concludes that Social VR holds transformative potential for reimagining human connections in digital spaces, contingent upon responsible development practices that prioritize safety, accessibility, and ethical design principles.